Agostinho e a sua crítica ao ceticismo no Contra acadêmicos - Cruz, Ruan Coutinho da (2017)
The present research has the purpose to analyze Augustine's counter-arguments to the skepticism in his work Contra Academicos. These arguments are: The issue of happiness, of the impossibility of knowing and of prescribing the suspension of judgement. These themes are defended inside the Academy, in the period led by Arcesilau and Carnéadas and went against Stoic doctrine. Augustine's phylosophical clash against the doctrine was not purely and exclusively theorical, but it had an existential view of life couse and his intelectual itinerary are treated as being clowely conected. An analysis about the structure of Contra Academicos and the concept of philosophia from the retreat of Cassiacico reveals the motivation and the reasons that led Augustine to undertake a struggle against the academic skepticism. The search and possession of the truth as something possible was Augustine's goal, and he identifies it as the person of Christ (wisdom of God). In an endearing way this work is an effort to offer the readers some knowledge about life, thoughts and nuances of young Augustine in this period.